Thiamine deficiency disorders: diagnosis, prevalence, and a roadmap for global control programs. Issue 1 (27th August 2018) - Whitfield, Kyly C.; Bourassa, Megan W.; Adamolekun, Bola; Bergeron, Gilles; Bettendorff, Lucien; Brown, Kenneth H.; Cox, Lorna; Fattal‐Valevski, Aviva; Fischer, Philip R.; Frank, Elizabeth L.; Hiffler, Laurent; Hlaing, Lwin Mar; et al.
Abstract: Thiamine is an essential micronutrient that plays a key role in energy metabolism. Many populations worldwide may be at risk of clinical or subclinical thiamine deficiencies, due to famine, reliance on staple crops with low thiamine content, or food preparation practices, such as milling grains and washing milled rice. Clinical manifestations of thiamine deficiency are variable; this, along with the lack of a readily accessible and widely agreed upon biomarker of thiamine status, complicates efforts to diagnose thiamine deficiency and assess its global prevalence. Strategies to identify regions at risk of thiamine deficiency through proxy measures, such as analysis of food balance sheet data and month‐specific infant mortality rates, may be valuable for understanding the scope of thiamine deficiency. Urgent public health responses are warranted in high‐risk regions, considering the contribution of thiamine deficiency to infant mortality and research suggesting that even subclinical thiamine deficiency in childhood may have lifelong neurodevelopmental consequences. Food fortification and maternal and/or infant thiamine supplementation have proven effective in raising thiamine status and reducing the incidence of infantile beriberi in regions where thiamine deficiency is prevalent, but trial data are limited. Efforts to determine culturally and environmentally appropriate food vehicles for thiamine fortification are ongoing. Abstract : This paper describes the current state of thiamine research and the significance of thiamine deficiency in low‐ and middle‐income countries from public health and clinical perspectives. The map shows countries where the estimated per capita availability of thiamine in the national food supply (as per food balance sheets) is below the recommended nutrient intake for men (in turquoise), and countries where rice or wheat flour fortification are in place to address low thiamine availability (in yellow).